APPROACHES AND THEORIES TO THE STUDY OF POLITICAL SPEECH - Harutyunyan, Rafayel (Armenian Folia Anglistika, 2021)
The article considers political discourse as a global unit attaching special significance to its linguistic characteristics that play an essential role in the formulation of political speech. The article reviews the theoretical background of the basic approaches and theories studying political speech and tries to outline their role in the context of the critical analysis of political discourse. The article also touches upon the main components of politics: language, action, conflict and cooperation, etc.